2013
DOI: 10.1186/1471-2458-13-1110
|View full text |Cite
|
Sign up to set email alerts
|

Associations between occupational indicators and total, work-based and leisure-time sitting: a cross-sectional study

Abstract: BackgroundA better understanding of how occupational indicators (e.g. job type, doing shift-work, hours worked, physical demand) influence sitting time will aid in the design of more effective health behaviour interventions. The aim of the study was to examine the associations between several occupational indicators and total, occupational and leisure-time sitting.MethodsCross-sectional self-report data was collected in November 2011 from 1194 participants through a telephone interview in regional Queensland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
51
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 38 publications
(69 reference statements)
15
51
4
3
Order By: Relevance
“…22,26 By contrast, sitting time was 1.5 times the amount of sitting time that has been reported in population samples of young and midaged Australian women 28 and more than two times higher than has been reported in the Australian general population. 16 This difference might be partially accounted for by the use of different questionnaires.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…22,26 By contrast, sitting time was 1.5 times the amount of sitting time that has been reported in population samples of young and midaged Australian women 28 and more than two times higher than has been reported in the Australian general population. 16 This difference might be partially accounted for by the use of different questionnaires.…”
Section: Discussionmentioning
confidence: 57%
“…16 This difference might be partially accounted for by the use of different questionnaires. For example, Bauman et al 16 used a singleitem total sitting time measure from the International Physical Activity Questionnaireshort form (IPAQ-short) to assess the sitting levels of Australian adults, whereas the present study and other studies 22,26 have used a domain-specific questionnaire. Moreover, given that the present study recruited employed adults who mostly sat for their working tasks, it is likely that the higher sitting volumes than those previously reported reflect the restriction of our sample to adults working in desk-based settings.…”
Section: Discussionmentioning
confidence: 98%
“…[55][56][57] In this study, participants in the control arm had mean daily step counts below the national average, supporting our hypothesis that this study population may be more sedentary. 36,37 Among participants in this study, 70 % had a BMI > 25 (overweight) and 39 % had a BMI > 30 (obese); further indication that these participants may be relatively sedentary. 58 Nevertheless, participants had a high engagement rate: 96.4 % of them completed the 26-week study despite no financial incentive of any kind during the follow-up period.…”
Section: Discussionmentioning
confidence: 66%
“…Many in this population had roles in which they were sitting most of the day and therefore may have been more sedentary than employees with more physically active roles. 36,37 Participants were excluded if they were already participating in another physical activity study, not able or willing to carry an iPhone or Android smartphone, currently pregnant or lactating, intending to become pregnant within the next 6 months, or stated any other reason that they did not expect to be able to complete the study.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…The predictors used for modelling in this study were Gupta et al selected a priori from the questionnaire based on (i) whether they would likely predict time spent sedentary or in physical activity according to previous studies (26,29,30,32,(36)(37)(38), (ii) whether they are commonly available in large epidemiological studies and surveys, and (iii) whether they showed a large relative dispersion between workers in our material. Based on these criteria, we arrived at including self-reported information on age, gender, body mass index (BMI), job type, OST, and OPA.…”
Section: Predictorsmentioning
confidence: 99%